2017
DOI: 10.1159/000476075
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism in the Aetiology of Caries: Systematic Literature Review

Abstract: Recent progress in the field of molecular biology and techniques of DNA sequence analysis allowed determining the meaning of hereditary factors of many common human diseases. Studies of genetic mechanisms in the aetiology of caries encompass, primarily, 4 main groups of genes responsible for (1) the development of enamel, (2) formation and composition of saliva, (3) immunological responses, and (4) carbohydrate metabolism. The aim of this study was to present current knowledge about the influence of single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(30 citation statements)
references
References 46 publications
1
25
0
2
Order By: Relevance
“…Previous studies have demonstrated that genes involved in enamel development are associated with caries susceptibility [Nibali et al, 2017;Piekoszewska-Ziętek et al, 2017] and DDE [Jeremias et al, 2013[Jeremias et al, , 2016. Our study proposes that the polymorphism rs478927 in MMP13 is involved in both conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that genes involved in enamel development are associated with caries susceptibility [Nibali et al, 2017;Piekoszewska-Ziętek et al, 2017] and DDE [Jeremias et al, 2013[Jeremias et al, , 2016. Our study proposes that the polymorphism rs478927 in MMP13 is involved in both conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Estimates of the disease variance proportion explained by genetics (often referred to as “heritability”) have ranged from 30% to 70%, with higher estimates found for primary versus permanent dentition caries. Numerous candidate‐gene studies have since been conducted to investigate the postulated role of several hypothesized genes in caries aetiology in children and adults. Studies in this body of literature have largely targeted enamel development and mineralization genes, as well as genes involved in the immune response in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies have shown a difference in the immunity response of both tasters and non-tasters to different types of cariogenic bacteria (Gil et al, 2015) and others (Farquhar et al, 2015;Verbeurgt et al, 2017). There are a variety of variations in genes associated with a high or low incidence of tooth decay (Piekoszewska-Ziętek et al, 2017); Thus, Dental caries is a multi-factorial disease and cannot be limited to only one factor or gene (Weber, 2016). The current study, although not confirm this relation in this sample, suggests that the presence or compatibility of a number of environmental and genetic factors may shape this association, including a variety of genes, for example, it was found that the heterozygote genotypes of TAS2R38 gene were associated with certain genetic patterns of CA6-encoded carbonic anhydrase 6; an enzyme important in regulating pH capacity of saliva, which in turn affects the degree of tooth consistency and non-erosion when saliva buffer capacity is low (Li et al, 2015;Melis et al, 2018;Esberg et al, 2019) So, the genetic makeup of an individual from many genes and differences in expression of these genes may affect this relation or explain it.…”
Section: Discussionmentioning
confidence: 99%